A review of silvopastoral systems in the Peruvian Amazon region - Eduardo Fuentes; Carlos Gómez; Dante Pizarro; Julio Alegre; Miguel Castillo; Jorge Vela; Ethel Huaman; Héctor Vásquez (Tropical Grasslands-Forrajes Tropicales, 2022)
Livestock in the Peruvian Amazon region is mostly produced in areas considered degraded pastureland and associated with deforestation. Silvopastoral systems (SPS) are an alternative for sustainable livestock production. This article aims to provide information about progress in development of SPS in the Peruvian Amazon region during the last 2 decades and opportunities to develop it further at the national level. The geographical characteristics and climatic conditions of the Peruvian Amazon are described, followed by a review of the experiences with SPS in the 5 most relevant departments of the region. Constraints for implementation of SPS practices in the country and the current initiatives at regional and national level to promote and develop more sustainable livestock production in the region are presented. There is a large variation in SPS practiced along the different departments of the Amazon region. It is imperative that the Peruvian Government continues promoting SPS for recovering degraded lands through generating enabling conditions for farmers to adopt and/or scale up SPS.